Flexible Electronics: Investigation of Nano‐Gaps in Fractured β‐Ga2O3 Nanomembranes Formed by Uniaxial Strain (Adv. Electron. Mater. 2/2021). (15th February 2021) - Hasan, Md Nazmul; Lai, Junyu; Swinnich, Edward; Zheng, Yixiong; Baboukani, Behnoosh Sattari; Nalam, Prathima C.; Seo, Jung‐Hun
Abstract : β‐Ga2 O3 nanomembranes are a quasi‐two‐dimensional form of bulk β‐Ga2 O3 . In article number 2000763, Jung‐Hun Seo and co‐workers present a systematical investigation of the layer delaminations and fractures in β‐Ga2 O3 nanomembrane under strain. The performance degradation is recovered by a water vapor treatment, meaning that this result provides a viable route for utilizing β‐Ga2 O3 nanomembrane as a material for future high‐performance flexible electronics.